(untitled) (Scientia Agricola, 2020)
The hydroponic growth system is a convenient platform for studying whole plant physiology, especially for root morphological and nutritional analysis. However, we found that most hydroponic systems described in the literature are not suitable for citrus plants. In this study, a hydroponic system for citrus was designed, comprising three principal components: power and time switch, aeration and hydroponic culture. Herein, details of the protocol were described, including equipment setup, seed pregermination and cultivation, together with preparation and transfer of nutrient solution into hydroponics. In order to demonstrate the adaptability of the trifoliate orange plant to our hydroponic system, comparative tests between soil- and hydroponically-grown plants were carried out. The results showed that the plants grew normally and there were no obvious differences between soil- and hydroponically-grown plants. In addition, nutrient deficiency and transcriptional analysis were carried out to test the efficiency, functionality and suitability of our hydroponic system for the application of physiological and molecular analysis. The results, compared with previous studies, showed that our hydroponic system delivered superior performance as regards the physiological and molecular analysis. Taken together, we established the culture system which is best suited for the growth of trifoliate oranges under hydroponic conditions. The hydroponic system described in this paper is easily constructed and controlled at a low cost. It may serve a wide gamut of experimental purposes, especially root morphological and nutritional analysis of trifoliate oranges and the system is also adaptable to other citrus plants by varying the device size.